PEMBELAJARAN IPS DENGAN MENGGUNAKAN METODE ROLE PLAYING DI SEKOLAH DASAR - FITRIANI, ISRA (Universitas Negeri Padang, 2014)
Abstract Based on the result of reflectionin the fourth grade of SDN 05 Pasia Laweh Kecamatan Palupuh, it was found out that the student learning out comes was still low. Therefore,this classroom action research was conducted. This research was conducted in two cycles. Each cycle consisted of planning, acting, observing and reflecting. The use of Role Playing required the researcher to do nine phases motivation of group, choose of actor, ready of observer, ready of step by actor, aktoring, discusi and remedi, aktor, discussion and evaluation, generalitation. The source of the data was the result of observation in every student’s activity in the five grade in Social Science by using Role Playing. Kata kunci: Metode Role Playing dan hasil belajar